Lie bialgebra structures on 2-step nilpotent graph algebras - Farinati, Marco Andrés (2018)
We generalize a result on the Heisenberg Lie algebra that gives restrictions to possible Lie bialgebra cobrackets on 2-step nilpotent algebras with some additional properties. For the class of 2-step nilpotent Lie algebras coming from graphs, we describe these extra properties in a very easy graph-combinatorial way. We exhibit applications for fn, the free 2-step nilpotent Lie algebra.